Computing with Spatial Trajectories - Zheng, Yu; Zheng, Yu; Zhou, Xiaofang (Computing with Spatial Trajectories, 2005)
Although there are many books on spatial databases, mobile computing, and data mining, this is the first book dedicated to computing with spatial trajectory data, with a broad spectrum of coverage and an authoritative overview. Aimed at advanced undergraduates, graduate students, researchers, and professionals, this book covers the major fundamentals and the key advanced topics that shape the field. Each chapter is a tutorial that provides readers with an introduction to one important aspect of computing with spatial trajectories and also contains many valuable references to relevant research papers. This book provides researchers and application developers a comprehensive overview of the general concepts, techniques, and applications of trajectory indexing, search, and data mining, and helps them explore this exciting field and develop new methods and applications. It also offers graduate students and other interested readers a general introduction to the most recent developments in this promising research area.